PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEAKTIFAN SISWA - Ade Nurlatifah; Septi Ambarwati (Universitas Sarjanawiyata Tamansiswa, 2017)
This research is aimed to find out the influences of cooperative learning Students Teams Achievement Division (STAD) type towards science learning outcome at eight grade students of SMP N 2 Banguntapan Bantul in the academic year 2016/2017 reviewed from students activeness. This research used a Quasi-Experiment. The object of research that used is learning the outcome. Data collection technique was taken by gave a test, questionnaire, and documentation technique. The instrument of the test consists of 30 multiple choice questions and the questionnaire consisted of 20 statements. The result of research obtained Famount=4,407 through p=0,037 and the average of learning outcome amount 20,06 and the result of questionnaire amount 74,00. Based on the result of learning outcome and questionnaire, there were influences of the use of cooperative learning on the Students Teams Achievement Division (STAD) type towards science learning outcome at eight grade students reviewed from students activeness